2009
DOI: 10.1002/hbm.20793
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of preparatory volitional motor cortical activity by paired associative transcranial magnetic stimulation

Abstract: Paired associative transcranial magnetic stimulation (PAS) has been shown to induce long-term potentiation (LTP)-like or long-term depression (LTD)-like change in excitability of human primary motor cortex (M1), as probed by motor evoked potential (MEP) amplitude. In contrast, little is known about PAS effects on volitional motor cortical activity. In 10 healthy subjects, movement related cortical potentials (MRCP) were recorded to index volitional motor cortical activity during preparation of simple thumb abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…A few studies explored EEG aftereffects after TBS (Katayama and Rothwell, 2007, Ishikawa et al, 2007), or PAS (Tsuji and Rothwell, 2002; Wolters et al, 2005). Aftereffects have been observed on a variety of EEG/EP-measures including oscillatory activity over motor and prefrontal areas (e.g., Strens et al, 2002 and Schutter et al, 2003) as well as somatosensory (e.g., Katayama and Rothwell, 2007; Ishikawa et al, 2007; Restuccia et al, 2007), visual (Schutter et al, 2003), cognitive (Evers et al, 2001a, b; Hansenne et al, 2004; Jing et al, 2001) and movement-related cortical potentials (Rossi et al, 2000; Lu et al, 2009), in accordance with the site of TMS. With three exceptions (Evers et al, 2001a, 2001b; Satow et al, 2003; Hansenne et al, 2004), all published studies reported significant aftereffects.…”
Section: Side Effectsmentioning
confidence: 65%
“…A few studies explored EEG aftereffects after TBS (Katayama and Rothwell, 2007, Ishikawa et al, 2007), or PAS (Tsuji and Rothwell, 2002; Wolters et al, 2005). Aftereffects have been observed on a variety of EEG/EP-measures including oscillatory activity over motor and prefrontal areas (e.g., Strens et al, 2002 and Schutter et al, 2003) as well as somatosensory (e.g., Katayama and Rothwell, 2007; Ishikawa et al, 2007; Restuccia et al, 2007), visual (Schutter et al, 2003), cognitive (Evers et al, 2001a, b; Hansenne et al, 2004; Jing et al, 2001) and movement-related cortical potentials (Rossi et al, 2000; Lu et al, 2009), in accordance with the site of TMS. With three exceptions (Evers et al, 2001a, 2001b; Satow et al, 2003; Hansenne et al, 2004), all published studies reported significant aftereffects.…”
Section: Side Effectsmentioning
confidence: 65%
“…The randomly alternating protocol was developed in our group originally for the conventional PAS protocol (i.e., pairing of electrical peripheral nerve stimulation with TMS of the contralateral M1 HAND ) where it did not induce any significant change of MEP amplitude (Müller et al, 2007; Lu et al, 2009). The intensity of CS was kept at 95% AMT determined over the inion.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are studies showing no change in MEPs during slight contractions (Kumpulainen et al, 2012;Stefan et al, 2000Stefan et al, , 2004. The interpretation of the effect of PAS on active muscles is more complicated as can be seen in the study of Lu et al (2009) where a decrease of the movement-related cortical potentials (MRCP) in electroencephalography recordings was reported after an LTPlike PAS-protocol. Accordingly, performing the same movement pattern, simple thumb abduction, generated a decreased MRCP negativity after the PAS intervention.…”
Section: Neural Correlates -Changes In Cortico-spinal and Spinal Excimentioning
confidence: 99%